Measuring variations of δ18O and δ2H in atmospheric water vapour using two commercial laser-based spectrometers: an instrument characterisation study - S. Pfahl; A. Knohl; H. Sodemann; P. Graf; P. Sturm; F. Aemisegger; H. Wernli (Atmospheric Measurement Techniques, 2012)
Variations of stable water isotopes in water vapour have become measurable at a measurement frequency of about 1 Hz in recent years using novel laser spectroscopic techniques. This enables us to perform continuous measurements for process-based investigations of the atmospheric water cycle at the time scales relevant for synoptic and mesoscale meteorology. An important prerequisite for the interpretation of data from automated field measurements lasting for several weeks or months is a detailed knowledge about instrument properties and the sources of measurement uncertainty. We present here a comprehensive characterisation and comparison study of two commercial laser spectroscopic systems based on cavity ring-down spectroscopy (Picarro) and off-axis integrated cavity output spectroscopy (Los Gatos Research). The uncertainty components of the measurements were first assessed in laboratory experiments, focussing on the effects of (i) water vapour mixing ratio, (ii) measurement stability, (iii) uncertainties due to calibration and (iv) response times of the isotope measurements due to adsorption-desorption processes on the tubing and measurement cavity walls. Based on the experience from our laboratory experiments, we set up a one-week field campaign for comparing measurements of the ambient isotope signals from the two laser spectroscopic systems. The optimal calibration strategy determined for both instruments was applied as well as the correction functions for water vapour mixing ratio effects. The root mean square difference between the isotope signals from the two instruments during the field deployment was 2.3‰ for δ2H, 0.5‰ for δ18O and 3.1‰ for deuterium excess. These uncertainty estimates from field measurements compare well to those found in the laboratory experiments. The present quality of measurements from laser spectroscopic instruments combined with a calibration system opens new possibilities for investigating the atmospheric water cycle and the land-atmosphere moisture fluxes.